Remittance and Trade Deficit Nexus in Nepal: A VECM Approach - Bhatta, Guna Raj (NRB Economic Review, 2013)
Once Nepal eased the access to the international labor market, there is an increasing trend of Nepalese working abroad, where annually thousands of young people migrate from the country. Consequently, there has been a sharp increment of remittance inflow in the recent years. Since remittance helps people improve the living standards, it has been observed as a good contributor for the poverty reduction in Nepal. Nevertheless, it might further deteriorate the trade balance, causing higher demand for consumable goods, most of which are imported in Nepal. Using cointegration techniques and a Vector Error Correction Model (VECM) based on the monthly data of merchandise import, worker's remittance and trade deficit for ten years period, this paper studies whether remittance causes the merchandise import and trade deficit to raise in the long run. The cointegration equation show that there is a long-run positive unidirectional causality from remittance to import as well as remittance to trade deficit implying that remittance causes merchandise import and deteriorates trade balance.